Conflict In The Church: The Uncomfortable Reality - John Paul Lathrop (Sekolah Tinggi Theologia Jaffray, 2015)
The apostle Paul, writing to Timothy, said “If anyone sets his heart on being an overseer, he desires a noble task” (1 Tim. 3:1, NIV). The work is definitely noble but the task is not always easy. Timothy knew that because he was in the troubled church of Ephesus at the time when Paul wrote to him. Paul also knew that the ministry is difficult. Conflict is all too often a part of Christian ministry. In this brief article, we explore three kinds of conflict that a minister may encounter in the church. Paul was experienced in all of them and so I will focus our attention on his experience.Rasul Paulus menuliskan kepada Timotius, katanya “Orang yang menghendaki jabatan penilik jemaat menginginkan pekerjaan yang indah” (1 Tim. 3:1, ITB). Pekerjaan ini memang sangat mulia namun tugas ini tidak selalu mudah. Timotius mengetahui hal itu karena ia berada dalam gereja yang bermasalah di Efesus pada saat itu Paulus menuliskan surat ini kepadanya. Paulus juga tahu bahwa pelayanan ini tidaklah mudah. Konflik yang terjadi merupakan bagian dari pelayanan orang Kristen. Dalam artikel ini, kita menyelidiki tiga jenis konflik yang mungkin akan dihadapi seorang pelayan di gereja. Saat itu Paulus mengalami semua konflik tersebut dan penulis akan fokus memberikan perhatian pada pengalaman pelayanannya.